Kajian Kitab Al Kasyaf Karya Zamakhsyari - Avif Alfiyah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
One of the many exegesis books circulating among Muslims is al-Kashshaf's commentary on al-Zamakhshari. This book of exegesis is a great book of value in terms of bayan, balaghah and other aspects of the miracles of the Qur'an. The depth of science and ability kebahasaannya able to issue a new face for tafsirnya so that it can reveal to us about the beauty of the Qur'an. This book is truly second to none in the field of exegesis and is an encyclopaedia for the 'ulama and reviewer of Tafseer. His critics have also admitted his beauty and goodness, though many of the teachings of mu'tazilah in them are the logical consequences of the ideology and school of the author of this book of exegesis, al-Zamakhshari.